Health Professionals' Perspectives of the Role of Palliative Care During COVID-19: Content Analysis of Articles and Blogs Posted on Twitter. (April 2022) - Singh, Gursharan K.; Rego, Joanna; Chambers, Shirley; Fox, Jennifer
Objective: The COVID-19 pandemic has resulted in health professionals facing unprecedented challenges and changes in practice. Responding to humanitarian crises involves saving lives and reducing suffering and as such, palliative care is an essential component of the response to COVID-19. This study aimed to explore health professionals' perspectives of the role of palliative care during the COVID-19 pandemic by analyzing their views and experiences expressed in articles and blogs located via Twitter. Method: Qualitative content analysis of 33 online articles and blogs written by health professionals from 1 February 2020 to 30 June 2020. Online articles and blogs were included if the URL was posted on Twitter. The consolidated criteria for reporting qualitative research (COREQ) guided data collection and reporting. Results: The health professionals whose viewpoints were analyzed were from Europe, North America, Oceania and Asia. The themes derived from content analysis were (a) the recognized value of palliative care during the pandemic, (b) positioning palliative care as every health professional's responsibility and (c) specialist palliative care supporting and guiding health professionals Conclusions: This study utilizes a unique approach to exploring the perspectives of health professionals from several countries during a global pandemic. The study emphasizes the value of palliative care and identifies gaps in end-of-life care provision including resource allocation. This brings to light the urgent need to equip all health professionals with palliative care knowledge and skills, including discussing and planning care. Specialist palliative care teams are well placed to support health professionals to provide quality care.